IMPLEMENTATION OF THE INDONESIAN CULTURE DIPLOMACY TOWARD AUSTRALIA THROUGH INDOFEST PERIOD 2012-2016 (CASE STUDY: ADELAIDE AND CANBERRA) - Ulyantraja Kelamor (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2018)
This journal discusses IndoFest activities which are conducted by Indonesia to Australia in 2012 to 2016 in Adelaide and Canberra. IndoFest was born in 2008, aims to introduce Indonesian culture in the international world. With the presence of IndoFest, it is also seen that cultural diplomacy continues to be done by Indonesia not only for improving good relations in both countries but also to introduce Indonesian art, culture, and exceptional food for more to the Australian people, in order to visit Indonesia. This journal also discusses Indonesia's cultural diplomacy towards Australia through IndoFest, as well as various activities in IndoFest to attract Australian tourists to come to Indonesia. As the research method, the qualitative method is used in this journal by library study, which is collecting the data from the literature related to the issue discussed. The results of the study stated that Indonesia successfully carried out its cultural diplomacy to Australia through IndoFest.